Diagnostic Yields, Charges, and Radiation Dose of Chest Imaging in Blunt Trauma Evaluations. (June 2014) - Rodriguez, Robert M.; Baumann, Brigitte M.; Raja, Ali S.; Langdorf, Mark I.; Anglin, Deirdre; Bradley, Richard N.; Medak, Anthony J.; Mower, William R.; Hendey, Gregory W.; Gratton, Matthew
Abstract Background Chest radiography (CXR) is the most common imaging in adult blunt trauma patient evaluation. Knowledge of the yields, attendant costs, and radiation doses delivered may guide effective chest imaging utilization. Objectives The objectives were to determine the diagnostic yields of blunt trauma chest imaging (CXR and chest computed tomography [CT]), to estimate charges and radiation exposure per injury identified, and to delineate assessment points in blunt trauma evaluation at which decision instruments for selective chest imaging would have the greatest effect. Methods From December 2009 to January 2012, we enrolled patients older than 14 years who received CXR during blunt trauma evaluations at nine U.S. Level I trauma centers in this prospective, observational study. Thoracic injury seen on chest imaging and clinical significance of the injury were defined by a trauma expert panel. Yields of imaging were calculated, as well as mean charges and effective radiation dose (ERD) per injury. Results Of 9, 905 enrolled patients, 55.4% had CXR alone, 42.0% had both CXR and CT, and 2.6% had CT alone. The yields for detecting thoracic injury were CXR 8.4% (95% confidence intervals [CIs]) = 7.8% to 8.9%), chest CT 28.8% (95% CI = 27.5% to 30.2%), and chest CT after normal CXR 15.0% (95% CI = 13.9% to 16.2%). The mean charges and ERD (millisievert [mSv]) per injury diagnosis of CXR, chest CT, and chest CT after normal CXR were $3, 845 (0.24 mSv), $10, 597 (30.9 mSv), and $20, 347 (59.3 mSv), respectively. The mean charges and ERD per clinically major thoracic injury diagnosis on chest CT after normal CXR were $203, 467 and 593 mSv. Conclusions Despite greater diagnostic yield, chest CT entails substantially higher charges and radiation dose per injury diagnosed, especially when performed after a normal CXR. Selective chest imaging decision instruments should identify patients who require no chest imaging and patients who may benefit from chest CT after a normal CXR.